2000
DOI: 10.1039/b005287f
|View full text |Cite
|
Sign up to set email alerts
|

Flow injection analysis of fluoride: optimization of experimental conditions and non-linear calibration using artificial neural networks

Abstract: Minimization of the background arising from the capillary wall is of extreme importance in laser induced fluorescence on-column detection for capillary electrophoresis. A sensitive confocal fluorescence detection scheme is described. The intense capillary wall background light was effectively rejected by an adjustable precision slit in a confocal configuration. Rhodamine 640 was used as a standard fluorophore. Detection linearity was demonstrated over four orders of magnitude of concentration and the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Zhou et al [38] established a linear combination of two variables, the peak height (H) and the residence time (T) as the response function (R F ). The aim is to maximize the peak height and minimize the residence time.…”
Section: Selection Of the Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al [38] established a linear combination of two variables, the peak height (H) and the residence time (T) as the response function (R F ). The aim is to maximize the peak height and minimize the residence time.…”
Section: Selection Of the Responsementioning
confidence: 99%
“…The objective function is a linear combination of different individual response variables and relies on three normalized factors. Zhou et al [38] used a linear combination of the peak height and the residence time as response function and a three-layer neural network for the optimisation of the spectrophotometric determination of fluoride. The optimisation performance of the artificial neural network was compared with that of a central composite design; the result showed that the artificial neural network provided better results that the central composite design for optimisation purposes.…”
Section: Natural Intelligence Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, on a first approximation, they could be used for modeling the behavior of calibration curves in atomic absorption spectrometry. Even though ANNs have received significant attention for spectrophotometric applications [19][20][21][22], their use in atomic spectrometry is relatively scarce [23][24][25].…”
Section: Introductionmentioning
confidence: 99%